2021
DOI: 10.5204/ijcjsd.2069
|View full text |Cite
|
Sign up to set email alerts
|

Locked Down with the Perpetrator: The Hidden Impacts of COVID-19 on Domestic and Family Violence in Australia

Abstract: Prior to the COVID-19 global pandemic, domestic and family violence (DFV) had been recognised globally as an epidemic in its own right. Further, research has established that during times of crisis and/or after disasters, rates of DFV can escalate. The COVID-19 pandemic has been no exception, with emerging research from around the world confirming that the public health measures and social effects associated with COVID-19 have increased the frequency and severity of DFV in various countries. In contributing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Women were also exposed during the pandemic to other negative consequences, with studies showing that in any crisis, the incidence of violent behaviour towards women increases. We point out in this regard that New Zealand reported a 53% increase in domestic violence following the 2010-2011 earthquakes, and research following Hurricane Katrina in 2005 led to the conclusion that violence against women increased by 98% during that period (Morley, 2021). In this new social normality, where isolation from the usual social network has become common, the search for adaptive states that provide security has become central.…”
Section: The Impact Of the Health Crisis On Vulnerable Urban Populationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Women were also exposed during the pandemic to other negative consequences, with studies showing that in any crisis, the incidence of violent behaviour towards women increases. We point out in this regard that New Zealand reported a 53% increase in domestic violence following the 2010-2011 earthquakes, and research following Hurricane Katrina in 2005 led to the conclusion that violence against women increased by 98% during that period (Morley, 2021). In this new social normality, where isolation from the usual social network has become common, the search for adaptive states that provide security has become central.…”
Section: The Impact Of the Health Crisis On Vulnerable Urban Populationsmentioning
confidence: 92%
“…In this new social normality, where isolation from the usual social network has become common, the search for adaptive states that provide security has become central. However, the pandemic has left women facing a complexity of problems that have manifested themselves in many forms, including greater financial hardship, insecurity or loss of employment and its associated social network, increased levels of stress, substance use and mental health problems, and not least, increased levels of domestic violence (Morley, 2021).…”
Section: The Impact Of the Health Crisis On Vulnerable Urban Populationsmentioning
confidence: 99%
“…The COVID-19 pandemic has raised concerns for a successive increase in domestic violence (DV; e.g., Hamadani et al, 2020; Hsu & Henke, 2021; Morley et al, 2021). However, relatively little is known of the frequency, consequences, and changes in types of violence experienced during the pandemic.…”
Section: In Previous Natural Disasters and Epidemicsmentioning
confidence: 99%
“…Consequently, the stay-at-home orders to mitigate COVID-19 have increased both risk and vulnerability for DV (e.g., Hsu & Henke, 2021). For example, an Australian survey study by Morley et al (2021) found that 86.5% of DV service providers reported increased complexity in their clients' needs due to the pandemic. These complex interactions contained greater overall job loss-related hardship, increased substance abuse, negative mental health, and more frequent and more severe DV.…”
mentioning
confidence: 99%
“…In June 2020, when the COVID-19 risk was low in SA, legal academics questioned 'the extent to which all of these measures remain necessary and proportionate to the threat posed by the pandemic in light of their impact on other competing public interests and on individual rights' (University of SA-Justice and Society Unit 2020: 1-2). Submissions revealed unease about the impact of movement restrictions on vulnerable people experiencing poverty, precarious housing or domestic violence (Law Society of South Australia 2020; Morley et al 2021). During the interviews, Tammy, a politician, and Sarah, a legal academic, questioned the capacity of the committee to meaningfully protect human rights.…”
Section: Emergency Powers and Covid-19 In Samentioning
confidence: 99%